GROWTH AND STRUCTURE OF THIN AU FILMS ON AG(111) - Fauster, Thomas; et al. (Physical Review B, 1994)
The growth and the structure of thin Au films on Ag(111) were studied by measuring the angular distribution of core-level photoelectrons emitted at high kinetic energy using a two-dimensional display-type electron spectrometer. Additional information was obtained by angle-integrated photoelectron spectroscopy and by thermal desorption spectrometry of NO. We find, even at room temperature, intermixing induced by surface diffusion. This conclusion is corroborated by the study of Au films deposited on (1-3)-monolayer-high Ag films grown on Pd(111).